A Karplus Equation for the Conformational Analysis of Organic Molecular Crystals1. Issue 45 (4th September 2019) - Thureau, Pierre; Carvin, Isaure; Ziarelli, Fabio; Viel, Stéphane; Mollica, Giulia
Abstract: Vicinal scalar couplings ( 3 J) are extensively used for the conformational analysis of organic compounds in the liquid state through empirical Karplus equations. In contrast, there are no examples of such use for the structural investigation of solids. With the support of first principles calculations, we demonstrate here that 13 C‐ 13 C 3 J coupling constants ( 3 JCC ) measured on a series of isotopically enriched solid amino acids and sugars can be related to dihedral angles by a simple Karplus‐like relationship, and we provide a parameterized Karplus function for the conformational analysis of organic molecular crystals. Under the experimental conditions discussed, torsional angles can be estimated from the experimental 3 JCC values with an accuracy of 10° using this function. These results open new perspectives towards the use of 3 JCC as a new analytical tool that could considerably simplify structure determination of functional organic solids. Abstract : A molecular goniometer for organic solids : Three‐bond J couplings accessed by solid‐state NMR spectroscopic analysis of organic solids are related to torsional angles through a simple Karplus relationship. This function constitutes a unique tool to probe the conformation of organic materials and is expected to significantly improve the determination of crystal structures for powders.